Clinical Decision Support for Hyperbilirubinemia Risk Assessment in the Electronic Health Record. - Petersen, John D.; Lozovatsky, Margaret; Markovic, Daniela; Duncan, Ray; Zheng, Simon; Shamsian, Arash; Kagele, Sonya; Ross, Mindy K. (Academic Pediatrics, 2020)
Physiologic neonatal hyperbilirubinemia (jaundice) is common and affects most newborn infants. However, there is a risk for permanent neurological damage if the bilirubin levels rise above a certain threshold. The management of neonatal jaundice includes the assessment of bilirubin laboratory values, consideration of patient-specific risk factors, and plotting on a bilirubin nomogram reference to determine risk and guide therapy. When performed manually, the process can be time consuming and error-prone. Therefore, web-based calculators such as BiliTool have been developed to assist in risk assessment. To streamline the risk assessment calculation process further within our electronic health record (EHR), we created a "BiliReport" to display patient bilirubin-related data and automate transmission of deidentified patient data to the BiliTool website (https://bilitool.org). After implementation, we evaluated usage data, provider satisfaction, and accuracy of documentation. We demonstrated high provider use of the BiliReport and satisfaction with the workflow. We found a significant improvement in the accuracy of bilirubin risk level documentation, with a reduction in erroneous risk stratification from 4% (15/232) to 0.4% (1/243), P < 0.001. We did not find significant a difference in erroneous documentation of the bilirubin lab value (P = 0.07). Integrating the neonatal hyperbilirubinemia risk assessment process into the EHR may reduce errors and improve provider documentation and adherence to recommended guidelines.